Sucrose dampens caffeine-induced blood pressure elevations – A randomized crossover pilot study in healthy, non-obese men - Ravussin, Yann; Montani, Jean-Pierre; Grasser, Erik Konrad (Frontiers in Nutrition, 2022)
Purpose: Sales for sugar-sweetened and caffeinated beverages are still rising globally and their consumption has been linked to the development of cardiovascular diseases. However, direct evidence from human interventional studies in response to such beverages are still scarce. Methods: Seven young, non-obese men participated in a randomized crossover study where four test drinks [60 g sucrose+50 mg caffeine, 60 g sucrose + caffeine-placebo, 50 mg caffeine, and caffeine-placebo)] were investigated. Each drink was brought to a total volume of 500 mL with water. Continuous and beat-to-beat hemodynamic monitoring was conducted for 30 min baseline and continued for 90 min after the ingestion of each drink. Measurements included blood pressure, heart rate, stroke volume, cardiac output, total peripheral resistance, index of contractility, and double product. Results: Two-factor ANOVA analysis revealed significant treatment-by-time effects for diastolic blood pressure, heart rate, stroke volume, cardiac output, total peripheral resistance, index of contractility, and double product (all p<0.01). Diastolic blood pressure and total peripheral resistance increased significantly to caffeine-only (all p<0.05), whilst sucrose + caffeine-placebo and sucrose + caffeine both decreased resistance responses (all p<0.05). Cardiac output increased significantly to sucrose + caffeine-placebo and sucrose + caffeine (all p<0.05), and on trend for heart rate, stroke volume and index of contractility (all p between 0.05 and 0.09). Conclusions: In young, non-obese men, a caffeinated and sucrose-sweetened beverage at concentrations similar to classical commercial Cola products exhibited distinct hemodynamic actions where the presence of sucrose dampened caffeine-induced blood pressure elevations, but at the expense of a tendency to increased cardiac work.